Metagestures - Nappi, Carla (punctum books, 2019)
"What kinds of knowledge and understandings of the world can be generated - and shared - when we use para-academic techniques and sensibilities to decode or respond to relatively orthodox intellectual objects? And what worlds might be possible if we practiced scholarly work from a place of collaboration and pleasure, as joyful fellow explorers? In Metagestures, presented in a playful tête-bêche format, historian Carla Nappi and cultural theorist Dominic Pettman explore the use of fiction as a tool to write and think with works of theory. Taking Vilém Flusser's Gestures as its point of inspiration and departure, Metagestures collects 16 pairs of short stories in which Pettman and Nappi make fictional worlds that animate and enliven each of the major gestures in Flusser's book. Nappi and Pettman focus on Flusser's mediations on the gestures of filming, planting, loving, smoking a pipe, turning a mask around, and much more, with their own creative explorations of each theme, in a gathering of short fictions that test, expand, and further the social scientific claims of the original text with new scenarios and occasions. Here, Flusser's reflections on physical gesture serve as an inspiration for new ways of conceiving and conducting theory, and for thoughtful creative scholarly imagining, with and alongside one another."